Decoding of the Story Superimposed of Buddhist Sculpture unearth from Bharja and testifying its relation to this Silk-route area of Sirohi District, India - Talesara, Priyank; Aniruddh Bahuguna, (Technium Social Sciences Journal, 2020)
Rohida police station recovered an old sculpture, accidentally discovered from the cemetery of Bharja/Bhaja village. It is a broken bronze Buddhist Idol and very rare sculpture. It has exquisite Antique beauty with rust in red and corrosion in green. Sculpture of Buddha seated in Padma Asana (lotus posture) and his hand in Dhyan Mudra (meditation posture). Buddha is wearing the robe; the robe is decorated with the scene of Buddhacharita story, superimposed on the visible crust. This Sirohi district has the history of Jainism and Hinduism only, till the date there is no evidence regarding Buddhism practices in Sirohi district of Rajasthan. Sirohi is famous from its silk route in the valley, ancient Chandrawati city and Mount Abu, where thousands of temples of Jainism and Shivanism were built. Objective: what were the technique and technology used to manufacture sculpture? Where this artefact came from? What are the main characteristics & features of this sculpture? What carving scene depicted in this sculpture? Research analysis: For analysis of this sculpture we carefully look sculpture and magnify scene to compare with the stories of Buddhacharita. Moreover, check out that this sculpture is indigenous work of ancestral craftsmen or not. Also compare superimposed stories of Buddha and his life. Scientific method: Buddha sculpture is hollow in nature but very heavy in weight; Craftsman used the lost wax method to manufacture it. In ancient time the science behind manufacturing sculpture is very time consuming, first sculptors need to imagine about the subject, draft and then mould through melting, condensing, chiselling, hammering and exquisite carving. One of the oldest methods of metal casting according to Archaeo-metallurgy is bee wax method; this technique is now termed as the lost wax method. Conclusion: In the end, we like to conclude that in the history of Sirohi exploration, first time unearths the Buddhist sculpture but we have certain doubts that it mustn’t belong to Sirohi district. This idol is required for further critical research like dating and detailed mould-casting technique used in the manufacturing of this sculpture.